Implicaciones literarias y filosóficas en la obra de Mario Lavista: siglo XX - López Pintor, Atenas (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
The mission of this investigation is to develop from the literary implications of the composition of Mario Lavista, the philosophical composition thought the Twentieth Century. In this sense, the investigation doesn’t seek to create a philosophy of music or a genealogy, but to restore the study of music through philosophy and finally, approach the sound expressions from an interdisciplinary area. This analysis replaces the tonal prejudice, the lack of meaning in the audition or the cataloging of noise music, from the reflective understanding of the sound of the Twentieth Century. Departing from the Mexican musician Mario Lavista´s work the study questions whether Twentieth Century music can only framed as the disintegration of form or from the creation of an ontological Gadamer bridge between the past and present. The investigation underscores the need for comprehensive integral education. From works such Aura, Simurg, Marsias and Reflections of the night, one concludes that the Twentieth Century music cannot be defined only as indeterminate, but as a plurality of languages coexisting in the same time or as an artistic game waiting to be unveiled. The Twentieth Century sound does not arise a complete break with its past, but also includes the presence of tonal compositions, the technological elements applied to traditional instruments, the linguistic vocal, the literary arguments and philosophical questions; namely, interdisciplinary relations as theater, poetry, architecture or painting, reflection on the essence of itself, the being of humanity. Finally, the Twentieth Century compositional belief does not only refer to the disintegration of the form or to the absence of its content. The significant content is experienced through musical reflection, the philosophy.

Esta investigación tiene como objetivo general desarrollar a partir de las implicaciones literarias de la composición de Mario Lavista, el pensamiento compositivo del siglo XX desde una reflexión filosófica (Gadamer, Schopenhauer, Adorno, Bloch, Fubini). En este sentido, la investigación no busca crear una filosofía de la música ni una genealogía, sino restablecer el estudio de la música a través de la filosofía y finalmente, acercarnos a las manifestaciones sonoras desde un ámbito interdisciplinario. El análisis sustituye los prejuicios tonales, las audiciones carentes de una falta de sentido o la catalogación de música de ruido, por una comprensión reflexiva del sonido del siglo. A partir de la obra del mexicano Mario Lavista, el estudio cuestiona si la música del siglo XX puede únicamente enmarcarse como la desintegración de la forma o desde otra posibilidad: la creación de un puente ontológico gadameriano entre el pasado y el presente musical; la necesidad de una educación integral. A partir de obras como Aura, Simurg, Marsias y Reflejos de la noche, se concluye que la música del siglo XX no puede ser definida únicamente como indeterminada, si no como una pluralidad de lenguajes conviviendo en una misma época o como un juego artístico esperando ser develado. La sonoridad del siglo no surge de una ruptura absoluta con su pasado, también abarca la presencia de composiciones tonales, la inclusión de elementos tecnológicos aplicados a instrumentos tradicionales, la integración lingüística vocal, argumentos literarios y cuestionamientos filosóficos; es decir, relaciones interdisciplinarias (teatro, poesía, arquitectura, pintura) reflexionando en el ser de sí misma, es ser de la humanidad. Finalmente, el pensamiento compositivo del siglo XX no refiere únicamente a la desintegración de la forma ni a la ausencia de su contenido. El contenido significativo se vivencia a través de la descodificación reflexiva de la música, la filosofía.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2013-1216; Literarias; Filosóficas; Siglo XX; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/99